Hedges Found in Young Learner’s Puss in Boots - Agnes Widyaningrum (Universitas Stikubank (UNISBANK) Semarang, 2015)
English children story book is an essential supplementary material for young readers to improve their English vocabulary. The student’s vocabulary will improve if they have good reading habit because if they do not want to read therefore their vocabulary remains the same. Learning English from the vocabulary is one kind of learning strategies done by the teachers who teach basic level. The more they read the English books the more vocabulary they will get. The story written by the author is related to their level. For elementary school students, the story book is created with many interesting colours and pictures. The design is suitable for them to arouse their curiosity so that they will read it. The sentences written in the story using simple structure aimed at helping the young readers to understand the content of the storybook. The sentences written are also containing hedges. Hedges are used in order to help young readers to know about politeness and to use English properly. This documentary study is analyzed in qualitative nature by giving detailed explanation for data. The step to collect the data is reading the books and the steps to analyze the data are identification, classification and interpretation. The result shows that there are hedges found in Young Learner’s book series with the purpose to teach young readers to learn politenes realized in hedges. Key words: vocabulary, learning strategy, hedges, politeness